Internal Labor Markets: A Worker Flow Approach - Ingrid Huitfeldt; Andreas Ravndal Kostøl; Jan Sebastian Nimczik; Andrea Weber (Institute of Labor Economics (IZA), 2021)
This paper develops a new method to study how workers' career and wage profiles are shaped by internal labor markets (ILM) and job hierarchies in firms. Our paper tackles the conceptual challenge of organizing jobs within firms into hierarchy levels by proposing a data-driven ranking method based on observed worker flows between occupations within firms. We apply our method to linked employer-employee data from Norway that records fine-grained occupational codes and tracks contract changes within firms. Our findings confirm existing evidence that is primarily based on case studies for single firms. We expand on this by documenting substantial heterogeneity in the structure and hierarchy of ILMs across a broad range of large firms. Our findings on wage and promotion dynamics in ILMs are consistent with models of careers in organizations.
Keywords: J31; J62; M5; 330; internal labor markets; organization of labor; wage setting